Assessing Microbial Water Quality, Users' Perceptions and System Functionality Following a Combined Water Safety Intervention in Rural Nepal - Bänziger, Carola; Schertenleib, Ariane; Kunwar, Bal Mukunda; Bhatta, Madan R.; Marks, Sara J. (Frontiers in Water, 2022)
Risk-based water safety interventions are one approach to improve drinking water quality and consequently reduce the number of people consuming faecally contaminated water. Despite broad acceptance of water safety planning approaches globally, there is a lack of evidence of their effectiveness for community-managed piped water supplies in rural areas of developing countries. Our research, in the form of a cluster-based controlled pre-post intervention analysis, investigates the impact of a combined water safety intervention on outcomes of microbial water quality, users’ perceptions and piped system functionality in rural Nepal. The study enrolled 21 treatment systems and 12 control systems across five districts of the Karnali and Sudurpaschim provinces. Treatment group interventions included field laboratories for microbial analysis, regular monitoring of water quality including sanitary inspections, targeted treatment and infrastructure improvements, household hygiene and water filter promotion, and community training. In certain systems, regular system-level chlorination was implemented. Before and after the interventions, the microbial water quality was measured at multiple points within the water system. This information was complemented by household interviews and sanitary inspections. The main result to emerge from this study is that chlorination is the only identified intervention that led to a significant reduction in E. coli concentration at the point of consumption. Secondly, the effectiveness of other interventions was presumably reduced due to higher contamination at endline in general, brought about by the monsoon. All the interventions had a positive impact on users’ perceptions about their water system, as measured by expectations for future functionality, satisfaction with the services received, and awareness of the potential health risks of drinking contaminated water. For future applications we would recommend the more broadly applied use of chlorination methods at system level as a key component of the package of risk-based water safety interventions.